Alpha project managers : what the top 2% know that everyone else does not - Crowe, Andy (Velociteach, 2006)
Debunking misconceptions surrounding successful project managers, this guide highlights the traits that make them stand out in the minds of their teams, senior managers, customers, and stakeholders. It offers key insights by providing multiple perspectives on the character makeup of the world's most successful project managers.